ANALISIS PENDAPATAN PETANI KAKAO DI DESA MOKUPA KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Asriani, Asriani; tajuddin, Tajuddin; Ariani, Wa Ode Rachmasari (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
Mokupa village has very good plantation potential. However, the development of cocoa production in Lambandia District, East Kolaka Regency from 2017 to 2021 tends to decline. In theory, a decrease in production will reduce purchasing power through a decrease in people's income so that purchasing power weakens. This will have an impact on the economy in Mokupa Village, Lambandia District, which works in the cocoa plantation sector. This study aims to determine the level of income of cocoa farmers in Mokupa Village, Lambandia District, East Kolaka Regency. Analyzed using income analysis, using the formula revenue, total cost, income. The results showed that the total production of cocoa farmers in Mokupa Village, Lambandia District, East Kolaka Regency obtained by farmers was 401 Kg with a selling price of IDR23.000/Kg, so that a total revenue of IDR 9.223.000/year, while the fixed costs incurred by farmers are IDR276.000/5 years, and the total variable costs are Rp. 2.838.150/year, so the total costs incurred are IDR 3.114.150/year. The total income of IDR 9,223,000/year earned by farmers is reduced by the total cost of IDR 3.114.150/year so that farmers' income is IDR. 6.108.850 / season / year.